2020
DOI: 10.3389/fmicb.2020.00752
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Phosphorus Solubilizing Bacteria With Multiple Phosphorus Sources Utilizing Capability and Their Potential for Lead Immobilization in Soil

Abstract: Phosphorus solubilizing bacteria (PSB) can promote the level of plant-absorbable phosphorus (P) in agro-ecosystems. However, little attention has been paid to PSB harboring abilities in utilizing multiple phosphorus sources and their potentials for heavy metal immobilization. In this study, we applied the strategy of stepwise acclimation by using Ca 3 (PO 4) 2 , phytate, FePO 4 , and AlPO 4 as sole P source. We gained 18 PSB possessing abilities of multiple P sources utilization, and these bacteria belonged to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 70 publications
5
68
0
3
Order By: Relevance
“…Genes encoding acid and alkaline phosphatases and a phytase were found in the genome of strain 169 ( Supplementary Table 1 ). Additionally, genes mediating polyphosphate formation ( ppk ) ( Wan et al, 2020 ) and phosphonoacetate degradation ( phnA ) ( Shariati et al, 2017 ) were present in the genome. Phosphate starvation-inducible glucose dehydrogenase (EC 1.1.5.2) encoded by the gcd gene may also be involved in the solubilization of mineral phosphates ( Sharma et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding acid and alkaline phosphatases and a phytase were found in the genome of strain 169 ( Supplementary Table 1 ). Additionally, genes mediating polyphosphate formation ( ppk ) ( Wan et al, 2020 ) and phosphonoacetate degradation ( phnA ) ( Shariati et al, 2017 ) were present in the genome. Phosphate starvation-inducible glucose dehydrogenase (EC 1.1.5.2) encoded by the gcd gene may also be involved in the solubilization of mineral phosphates ( Sharma et al, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…Burkholderia sp., Enterobacter sp., Pseudomonas sp., and Staphylococcus sp. are the most prominent phytate solublizers [46,47,48]. Kumar et al [39] found in a study that Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…All the three potential strains efficiently solubilized CP and SP and produced halo zone around spot inoculation indicating the release of free P. Plant growth promoting rhizobacteria such as Bacillus sp., Burkholderia sp., Enterobacter sp., Pseudomonas sp., and Staphylococcus sp. are the most prominent phytate solublizers [ 46 , 47 , 48 ]. Kumar et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, since pqqA, pqqB, pqqC, pqqD, and pqqE genes are conserved and arranged in that order in the pqq operon (pqqABCDE) (Shen et al, 2012), we selected the pqqB and pqqE genes to study the mPSB. Given the substantial wide distribution of PSB in natural ecosystems including soils, freshwater, seawater, and sediments (Zhang et al, 2015;Liang et al, 2020;Wan et al, 2020), we cannot completely rule out a possible contribution of phosphate solubilizing bacteria in the increase of P fractions in our compost treatments. The moderate but positive correlation of 16S bacteria with the labile-P supports the possibility of bacteria to intervene in the P solubilization in the composts.…”
Section: Relationships Between Compost's P Fractions and Microbiologimentioning
confidence: 99%